2017
DOI: 10.1159/000472407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BRD4 Suppresses Cell Proliferation and Induces Apoptosis in Renal Cell Carcinoma

Abstract: Background/Aims: Renal cell carcinoma (RCC) remains an intractable genitourinary malignancy. Resistance to chemotherapy or targeted therapies in RCC is presumably due to the complicated underlying molecular mechanisms and insufficient understanding. The aim of this research was to assess the expression and role of bromodomain-4 protein (BRD4) in RCC and evaluate the effects of BRD4 inhibitor JQ1 for RCC treatment. Methods: BRD4 expressionlevels were assessed by qRT-PCR and western blot in RCC tissues and cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…These findings support the hypothesis that different mechanisms may be responsible for the efficacy of JQ1 in NETs, and these may involve the apoptotic pathway, as indicated by our RNA-Seq analysis that revealed four apoptosis-associated genes (Capn9, Dffb, Birc3 and Nfkb1) to be downregulated by JQ1 treatment. Birc3 encodes cIAP2, which is an E3 ubiquitin protein ligase that is a member of the inhibitors of apoptosis proteins (IAP) family, and increases cIAP2 expression that can lead to evasion of caspase-mediated apoptosis in different cancers including gastric and gallbladder cancers and glioblastoma (Wang et al 2016, Jiang et al 2017, Gowda Saralamma et al 2018. In addition, cIAP2 has been reported to activate NFκB (encoded by Nfkb1) signalling, which also has roles in apoptosis regulation (Tchoghandjian et al 2013, Jiang et al 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the hypothesis that different mechanisms may be responsible for the efficacy of JQ1 in NETs, and these may involve the apoptotic pathway, as indicated by our RNA-Seq analysis that revealed four apoptosis-associated genes (Capn9, Dffb, Birc3 and Nfkb1) to be downregulated by JQ1 treatment. Birc3 encodes cIAP2, which is an E3 ubiquitin protein ligase that is a member of the inhibitors of apoptosis proteins (IAP) family, and increases cIAP2 expression that can lead to evasion of caspase-mediated apoptosis in different cancers including gastric and gallbladder cancers and glioblastoma (Wang et al 2016, Jiang et al 2017, Gowda Saralamma et al 2018. In addition, cIAP2 has been reported to activate NFκB (encoded by Nfkb1) signalling, which also has roles in apoptosis regulation (Tchoghandjian et al 2013, Jiang et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic-targeting compounds are a new class of anti-tumour drugs, and one such family of small molecule bromo and extra-terminal domain (BET) inhibitors, which target the bromodomains (BRDs) of the protein family members BRD2, BRD3, BRD4 and BRDT that bind acetylated residues on histones that regulate gene expression, and particularly those of tissue-specific genes (Filippakopoulos et al 2010), have been shown in preclinical in vitro and in vivo studies to have efficacy in a number of tumour types including pancreatic neuroendocrine tumours, glioma, nuclear protein in testis (NUT)-midline carcinoma, leukaemias and renal cell carcinoma (Beesley et al 2014, Coude et al 2015, Ishida et al 2017a,b, Leal et al 2017, Lines et al 2017, Wu et al 2017. Moreover, in order to determine if BET inhibitors may also represent an effective novel therapy for corticotrophinomas in reducing proliferation and increasing apoptosis of these pituitary cells, we first investigated the mouse corticotroph tumour cell line AtT20 for expression of the BET protein family members and then the effects of the BET inhibitors JQ1 and PFI-1 on proliferation, apoptosis and ACTH secretion by these pituitary cells.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in the case of BET‐inhibitors, genomic evidence was observed from the PDCs established from both RCC.1 and RCC.3 suggesting that epigenetic mechanisms should be further explored in RCC for clinical relevance. The pro‐oncogenic role of BRD4 was recently evaluated in RCC through in vitro and in vivo experiments, which also suggested a treatment rationale for RCC patients …”
Section: Discussionmentioning
confidence: 99%
“…Forty micrograms of lysate proteins per lane were separated on 10-12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (PAGE) gels, then transferred to polyvinylidene difluoride (PVDF) membrane (Millipore, Suzhou, China) [22]. After blocking, the blots were incubated with the appropriate primary and secondary antibodies.…”
Section: Western Blotmentioning
confidence: 99%